Dark alumina for novel solar receivers. (February 2020) - Sani, Elisa; Failla, Simone; Sciti, Diletta
Abstract: Concentrating solar power is one of the most promising solar energy exploitation technologies. Its efficiency improvement needs a significant increase of operating temperatures, from the current 500 °C to 900 °C. Alumina (Al2 O3 ) ceramics are refractory materials characterized by a huge industrial interest, mature production techniques and low cost. In the present work, we successfully synthesized dark ceramic Al2 O3 bulks, to evaluate their potential as high-temperature solar absorbers for CSP. We investigated process-dependent ceramics composition, microstructure and optical properties, obtaining pellets with a solar absorbance even higher than that of SiC. Graphical abstract: Image, graphical abstract